1980
DOI: 10.1172/jci109733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melanotropic peptides on fetal adrenal gland.

Abstract: A B S T R A C T Adrenal glands from early, mid, and late fetuses of rabbit, guinea pig, and rat, and from newborn animals of each species, were incubated for 1-4 h with and without 0.1 nM-1 ,uM ACTH, a-or ,B-melanocyte-stimulating hormone (aMSH or ,3MSH).The effects of the peptides were measured on production of glucocorticoids, and on incorporation of labeled thymidine or leucine into DNA or protein, respectively. The findings were similar in all three species. ACTH stimulated synthesis of glucocorticoids thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

1981
1981
2001
2001

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
2
15
1
Order By: Relevance
“…A similar trophic effect of a-MSH on adrenal gland was also reported in the fetus (22). Considering the negative correlation existing between DHEA-S and a-MSH response to domperidone, the actual study suggests that a role for a-MSH could possibly be hypothesized also for human adrenarche (22).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A similar trophic effect of a-MSH on adrenal gland was also reported in the fetus (22). Considering the negative correlation existing between DHEA-S and a-MSH response to domperidone, the actual study suggests that a role for a-MSH could possibly be hypothesized also for human adrenarche (22).…”
Section: Discussionsupporting
confidence: 74%
“…Confirming the in vitro steroidogenic effects of melanotropic hormones, such a treatment was accompanied by an increase in the ACTH 1-13 pituitary content (21). A similar trophic effect of a-MSH on adrenal gland was also reported in the fetus (22). Considering the negative correlation existing between DHEA-S and a-MSH response to domperidone, the actual study suggests that a role for a-MSH could possibly be hypothesized also for human adrenarche (22).…”
Section: Discussionsupporting
confidence: 72%
“…In this regard it is noteworthy that recently Coates et al [17] demonstrated that desacetyl-a-MSH is the major form of a-MSH in a-MSH-containing isles located inside human adult anterior hypophysis and, additionally, a-MSH re lease does not seem to need previous acetylation in mammals [18], The functional significance of desacetyla-MSH and of its changes during the menstrual cycle as well, is unknown at present. Like a-MSH, desacetyl-a-MSH might participate in the regulation of the adrenal function [ 19,20] or exert a trophic action on the adrenal tissue [21,22]. Furthermore, a-MSH peptides are con sidered to be endogenous antagonists of opioid peptides [23], Since opioid peptides have profound effects on reproductive functions especially on the ovulatory pro cess [24,25], it is tempting to speculate that the various forms of a-MSH might have the role of counteracting opioid function in this crucial event of the reproductive process.…”
Section: Discussionmentioning
confidence: 99%
“…The tryptic and chymotryptic maps, however, demonstrate that product I is neither a-melanotropin nor des-AcaN-r-melanotropin. It also cannot be the recently described bovine melanotropic peptide [N, O-diacetyl-serine'la-melanotropin [22], as a (c1iymo)tryptic map of this latter peptide would, with the exception of the N-terminal fragment, correspond to that of a-melanotropin. Neither are its mapping characteristics consistent with a /3-melanotropin-like structure.…”
Section: Melanotropin-relaied Pepiidesmentioning
confidence: 83%